Chinese correspondence in Dutch East Indies (1865-1949) - Siem, Tjong Han (Wacana, Journal of the Humanities of Indonesia, 2017)
This article is an attempt to describe some aspects of the social history of the Chinese minority in the Dutch East Indies using items of postal history as a guide. It is a very personal view, seen through the eyes of a philatelist. Using a postal history collection, aspects of political history can be illustrated and/or documented. This article is certainly not to be read as a solid, documented scientific exercise. It should be read in the spirit of educational entertainment.